Prosperity level and income distribution of coconut sugar craftsmen in banyumas district - Lilis Siti Badriah; Arintoko Arintoko; Dijan Rahajuni (INOVASI, 2022)
The purpose of this study was to analyze the income and prosperity of coconut sugar craftsmen in Cilongok Sub-District, especially in Batuanten Village, as one of the areas with the highest number of penderes in Cilongok Sub-District. This study uses primary data from 53 respondents of coconut sugar craftsmen. To analyze the level of prosperity, it is by comparing the per capita income of the craftsman's family with the rural poverty line in Indonesia in 2021. Meanwhile, to analyze the inequality of income distribution, the Gini Ratio is used. The results showed that the life level of coconut sugar craftsmen was still below the rural poverty line. The level of income distribution of craftsmen seen from their main source of income and also from family income, is in a low level of inequality, but this inequality is in a low level of income so that it is vulnerable to shocks. Meanwhile, when viewed from other sources of income, the level of inequality is high. The implication is that to increase prosperity and equitable distribution of income for coconut sugar craftsmen, efforts are needed to develop other sources of family income. For this reason, the support of various competent parties is needed to help the craftsmen and their families increase family income and to maintain the sustainability of coconut sugar production. The novelty of this research is to analyze the condition of prosperity and income distribution of coconut sugar craftsmen in Batuanten Village in 2021 during the pandemic era.